On the Vestiges of the Forest of Cree, in Galloway (Proceedings of the Society of Antiquaries of Scotland, 1864)
The author argues that there was an ancient forest along the river Cree between Newton Stewart and the Bay of Wigtown in Dumfries and Galloway. He briefly describes the contemporary terrain and describes the submerged tree trunks and roots that are found on the riverbed. The unusual size of these trees is also noted. An attempt at estimating when these trees were aboveground is made by examining artefacts found at the same depth as the trees on the riverbed, including oak canoes, various stone tools and what may be a Roman battle-axe. Meeting notes for 9 February, 1863 are appended.